2021
DOI: 10.25081/jmhe.2021.v7.6309
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxic potential of gel extract of Aloe vera against Sodium azide genotoxicity in Allium cepa cells

Abstract: Nowadays, the increasing rate of human exposure to various kinds of environmental mutagens has necessitated the search for natural antimutagens /antigenotoxic agents in natural products. In this study, Aloe vera gel extract was tested for its possible antigenotoxicity following the Allium cepa assay. Ten onions (Allium cepa) per dose were grown for 48 and 72 hours on gel extract of A. vera at 6.25%, 12.5%, 25.0%, 50.0% and 100.0% in combination with sodium azide (0.05mg/ml) solution for microscopic and macrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…O composto é reconhecido por sua capacidade de induzir aberrações cromossômicas, incluindo aderências anormais, formação de pontes, alterações na divisão mitótica, presença de cromossomos vagantes, anomalias nas estruturas nucleares celulares, desordens no funcionamento do fusomitótico e até mesmo ocorrência de quebras cromossômicas. Além de que, também possui capacidade de impedir a condensação da cromatina e diminuir o índice mitótico (Prieto et al, 2006;Abdulrahaman et al, 2018;Akinboro;Jimoh, 2021). Contudo, é importante ressaltar que um aspecto desfavorável da AS é sua resposta mutagênica variável, influenciada pelo pH da solução de tratamento.…”
Section: Fonte: Autoresunclassified
“…O composto é reconhecido por sua capacidade de induzir aberrações cromossômicas, incluindo aderências anormais, formação de pontes, alterações na divisão mitótica, presença de cromossomos vagantes, anomalias nas estruturas nucleares celulares, desordens no funcionamento do fusomitótico e até mesmo ocorrência de quebras cromossômicas. Além de que, também possui capacidade de impedir a condensação da cromatina e diminuir o índice mitótico (Prieto et al, 2006;Abdulrahaman et al, 2018;Akinboro;Jimoh, 2021). Contudo, é importante ressaltar que um aspecto desfavorável da AS é sua resposta mutagênica variável, influenciada pelo pH da solução de tratamento.…”
Section: Fonte: Autoresunclassified
“…is a clear and gel-like substance obtained from A. vera leaf [13]. A. vera plant is known to contain active components such as vitamins, enzymes, minerals, sugars, lignin, saponins, salicylic acids and amino acids [14]. It is reported that A. vera, which has anticarcinogenic, antibacterial, antiviral, antiinflammatory and antioxidant activities, reduces the genotoxic effect of D. melanogaster reduced genotoxicity after D. melanogaster had mutated with ethyl methanesulfonate (EMS) [15].…”
Section: Highlightsmentioning
confidence: 99%
“…The powder of each plant and that of the recipe in separate glass jars was added with five hundred milliliters of distilled water and then placed inside a water bath set at 64°C for 2 hours 15 minutes. The single extract and recipe were allowed to cool down before sieving each through a Whatman filter paper (No 1) and stored in a refrigerator at 4ºC for further use (Akinboro et al, 2017;Akinboro and Jimoh, 2021a).…”
Section: Preparation Of Plant Extractsmentioning
confidence: 99%
“…They were sun dried for two weeks to reduce moisture content so as to facilitate root growth. The onions were descaled carefully using a razor blade, leaving intact the primordial root ring (Akinboro et al, 2020b;Akinboro et al, 2021aAkinboro et al, , 2021b. The onions were rinsed with distilled water and wiped with tissue paper.…”
Section: Determination Of Total Proteinmentioning
confidence: 99%
See 1 more Smart Citation